Landscape drawing step by step - Blake, Wendon; Petrie, Ferdinand, 1925- (Mineola, N.Y. : Dover Publications, 1998)
Step-by-step demonstrations of landscape and coastal scenes; how to establish linear and aerial perspectives, transform cubical, cylindrical, rounded, and irregular shapes into natural forms and geographical features; and how best to use pencil, chalk, charcoal and tools.
Keywords: Landscape drawing -- Technique